(untitled) (Journal of Science and Technology, 2016)
The physical, thermal and mechanical proper-ties of some clay and non-clay raw materials usually used for the manufacture of high alumina refractory bricks have been determined. The effects of coarse and fine grain sizes on the physical and mechanical properties were also investigated. The clay materials (Yakusa Kibushi clay, elutriated plastic clay and hard shale clay) exhibited large shrinkages (17-30%) and large weight losses (14-19%). The calcined clay or grog, on the other hand, had small volume shrinkages (up to 8%) and weight losses (up to 7%). The porosity of bricks prepared from a mixture of coarse (0.297-3.36 mm) and fine (under 0.297 mm) grains was on the average 27% lower than that made of only fine grains. Bulk densities of coarse-and-fine-grained clay bricks were larger than the corresponding values for the fine-grained bricks. The values for cold crushing strength were observed to be dependent on the bulk density, apparent porosity, the alumina content and the grain size distribution of the raw materials. The refractoriness of the raw materials increased with the alumina content.